Design Of Speed, Agility, Quickness Exercises To Improve The Physical Fitness Of Students At The Muhammadiyah University Of Surakarta In Terms Of Speed and Endurance - Nur Subekti; Agam Akhmad Syaukani; Anugrah Nur Warthadi; Amar Abdullah Dani Arni Raihan; Raihan Budianto (UNIB Press, 2021)
The purpose of this study was to determine the design of speed, agility, quickness exercises to improve the physical fitness of students at the Muhammadiyah University of Surakarta. The sample of this study was male students at the Sport Education Study Program, Faculty of Teacher Training and Education, Muhammadiyah University of Surakarta, with some 40 people, purposive sampling was used to determine the sample. This research method uses quasi-experimental research. Data analysis techniques use the constellation one group pretest_posttest design. Data analysis techniques use descriptive analysis and inferential analysis, descriptive analysis is used to describe the results of this study while inferential analysis uses paired sample tests at a significant level ? =0.05 analysis used with the help of SPSS version 20.0. The results of this study can be concluded. Speed, Agility and Quickness (SAQ) training models namely:(1)